Zapatistas rebellion from the grassroots to the global - Khasnabish, Alex (Fernwood Publ. [u.a.], 2010)
"In the early hours of January 1, 1994 a guerrilla army of indigenous Mayan peasants emerged from the highlands and jungle in the far southeast of Mexico and declared "¡Ya basta!" -- "Enough!" -- to 500 years of colonialism, racism, exploitation, oppression, and genocide. As elites in Canada, the United States, and Mexico celebrated the coming into force of the North American Free Trade Agreement the Zapatista Army of National Liberation (Ejercito Zapatista de Liberacion Nacional, EZLN) declared war against this 500 year old trajectory toward oblivion, one that they said was most recently reincarnated in the form of neoliberal capitalist globalization that NAFTA represented. While the Zapatista uprising would have a profound impact upon the socio-political fabric of Chiapas its effects would be felt far beyond the borders of Mexico. At a moment when state-sponsored socialism had all but vanished from the global political landscape and other familiar elements of the left appeared utterly demoralized and defeated in the face of neoliberal capitalism's global ascendance, the Zapatista uprising would spark an unexpected and powerful new wave of radical socio-political action transnationally. Through an exploration of the Zapatista movement's origins, history, structure, aims, political philosophy and practice, and future directions this book provides a critical, comprehensive, and accessible overview of one of the most important rebel groups in recent history." -- Publisher description
Includes bibliographical references (p. [205]-214) and index
'Enough!' : introduction -- 'We are the product of five hundred years of resistance' : the origins of Zapatismo -- 'Everything for everyone, nothing for ourselves' : Zapatismo as political philosophy and political practice -- 'Never again a Mexico without us' : the national impact of Zapatismo -- 'A world made of many worlds' : the transnational impact of Zapatismo -- 'To open a crack in history' : conclusion
Keywords: Ejército Zapatista de Liberación Nacional (Mexico) / History; Ejército Zapatista de Liberación Nacional (Mexico) / Influence; Ejército Zapatista de Liberación Nacional (Mexique) / Histoire; Ejército Zapatista de Liberación Nacional; Geschichte 1900-2000; Indians of Mexico / Mexico / Chiapas / Social conditions / 20th century; Social movements / Mexico / Chiapas / History / 20th century; Socialism / Latin America; Anti-globalization movement; Indiens d'Amérique / Mexique / Chiapas / Conditions sociales / 20e siècle; Mouvements sociaux / Mexique / Chiapas / Histoire / 20e siècle; Verzet; Geschichte; Chiapas (Mexico) / History / Peasant Uprising, 1994-; Chiapas (Mexique) / Histoire / 1994 (Révolte paysanne); Mexico; Lateinamerika; Mexiko